PEMBUATAN PUPUK ORGANIK LIMBAH KULIT PISANG (Musa paradisiaca) DAN Mucuna brakteata DENGAN MENGGUNAKAN BIOAKTIVAKTOR EFFECTIVE MICROORGANISME (EM4) - Yuanita; F. Silvi Dwi Mentari; Faradilla; Rusmini (JURNAL AGRIMENT, 2022)
Organic fertilizers are fertilizers derived from the weathering of organic materials in the form of plant remains, animal waste and can come from household waste or industrial waste. One of the organic materials that can be made into solid organic fertilizer is banana peel waste and mucuna brakteata. The process of making solid organic fertilizer by adding soluble Effective microorganisms (EM 4) accelerates the composting process well.This study aims to observe the physical properties of fertilizers (color, odor, shape and temperature of the compost) and chemical properties or analyze the nutrient content of compost fertilizers from banana peels and Mucuna brakteata with Bioactivator Effective Microorganisms (EM4). This research was carried out at the Production Laboratory of the Plantation Cultivation Study Program and the Soil Science Laboratory of the Samarinda State Agricultural Polytechnic. The results of the research on making organic fertilizer from waste from banana peels and mucuna bracteata as the basic ingredient of accelerated fertilizer using EM4 solution for 16 days until ripe, visible from blackish color, odorless, crumb form (crushed when kneaded) and normal temperature (27OC). ). Contains nutrients N 1.148%, P 0.237%, K 0.459%, C-Organic 12.19%, C/N 10.618 and pH 7.8. In accordance with the compost quality standard SNI 19-7030-2004